Evaluation of "First Contact Access" for children using the PCATool- Brazil (Research, Society and Development, 2021)
The study aimed to evaluate the quality of first contact access in the childcare consultation in a Family Health Strategy (FHS) from the perspective of children's caregivers, using PCATool as an instrument. Descriptive and cross-sectional study, with a quantitative approach developed in the FHS of a city in the Fronteira-Oeste of Rio Grande do Sul, Brazil. 34 caregivers participated of the study, which are responsible for children aged 0 to 5 years and whom perform childcare at the FHS and attend the unit. Most were mothers or grandmothers (97%), married (70.6%), with one child (32.4%) and with their own house (82.4%). Policies encourage services to promote childcare consultations reaching all children in their population. The fragility in the population's access to childcare consultation can be seen in other studies that bring mobility difficulties and in scheduling the day and time for consultation as the main reasons for low adherence. The access of individuals regarding care, time to obtain consultation and difficulty in obtaining medical care obtained, in the great majority, satisfactory answers. The waiting time and telephone counseling obtained less than expected results, raising the hypothesis that they are reasons for the families may choose not to continue the monitoring. There is a need for improvement of the team in the accessibility of users to childcare consultation, starting from new studies referring to the main related barriers and actions to be instituted to expand the population's access in the monitoring of the child.